Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Tsiros, M.; Coates, A.; Howe, P.; Grimshaw, P.; Walkley, J.; Shield, A.; Mallows, R.; Hills, A.; Kagawa, Masaharu; Shultz, S.; Buckley, J. (Springer-Verlag, 2013)
The purpose of this study was to investigate if obese children have reduced knee extensor (KE) strength and to explore the relationship between adiposity and KE strength. An observational case-control study was conducted in three Australian states, recruiting obese [N = 107 (51 female, 56 male)] and healthy-weight [N = 132 (56 female, 76 male)] 10- to 13-year-old children. Body mass index, body composition (dual energy X-ray absorptiometry), isokinetic/isometric peak KE torques (dynamometry) and physical activity (accelerometry) were assessed. Results revealed that compared with their healthy-weight peers, obese children had higher absolute KE torques (P = 0.005), equivocal KE torques when allometrically normalized for fat-free mass (FFM) (P = 0.448) but lower relative KE torques when allometrically normalized for body mass (P = 0.008). Adjustments for maternal education, income and accelerometry had little impact on group differences, except for isometric KE torques relative to body mass which were no longer significantly lower in obese children (P = 0.013, not significant after controlling for multiple comparisons). Percent body fat was inversely related to KE torques relative to body mass (r = -0.22 to -0.35, P = 0.002), irrespective of maternal education, income or accelerometry. In conclusion, while obese children have higher absolute KE strength and FFM, they have less functional KE strength (relative to mass) available for weight-bearing activities than healthy-weight children. The finding that FFM-normalized KE torques did not differ suggests that the intrinsic contractile properties of the KE muscles are unaffected by obesity. Future research is needed to see if deficits in KE strength relative to mass translate into functional limitations in weight-bearing activities. © 2012 Springer-Verlag Berlin Heidelberg.